Inelastic Behavior of Steel X-Bracings with Back-To-Back Channel Sections: A Numerical Study - Tjahjanto, Helmy Hermawan; Livana, Jazlyn; Wisena, Perceka; Wijaya, Paulus Karta (Applied Research on Civil Engineering and Environment (ARCEE), 2024)
There are two approaches in determining compression capacity of braces in X-bracing type of concentrically braced frames (CBFs) where the compression braces are connected and interacted with the tension braces. One approach is assuming the effective length factor, K, of the braces to be taken as 0.5, while the other approaches suggest more conservative K values and indicate that the compression braces behavior might be affected by the tension braces and connection plates stiffness. Finite element analyses using ABAQUS are conducted evaluate the nonlinear behavior of X-bracings with back-to-back channel sections with varied slenderness ratio and gusset plates flexural stiffness. From the analytical results, it is found that in all evaluated configurations, yielding in tension braces occurs before buckling of compression braces. Although behave inelastically, the tension braces could act as partial restraints for the compression braces at the intersection points, resulting symmetrical buckling shapes when the compression braces reach their axial capacity. Equivalent effective length factors, which are determined from back calculations based on AISC360-22 formulations for compression members, are ranged from 0.36 to 0.46 and from 0.70 to 0.82, for braces with higher and lower slenderness ratios, respectively. Yielding of gusset plates indicates that the corresponding brace lengths should be measured between the designated fold lines. Gusset plates flexural stiffness could also contribute to the compression capacity of the braces.